In Vitro Apatite Deposition on TiO2 Film Derived from Electro-Chemical Treatment on Ti Substrate under Mixed Acid Electrolyte - Elfallah, Saleh S Saleh; Abdullah, Hasan Zuhudi (International Journal of Integrated Engineering, 2018)
Anodic oxidation is used to produce thick titania (TiO2) coating layer in a mixture of acids electrolyte to modify the TiO2 which is naturally formed on titanium (Ti) with a thickness of only a few nanometers and inert. The TiO2 coating is then subjected to an in-vitro test to evaluate their bioactivity in simulation body fluid (SBF). In the present work, oxide coatings of TiO2 were formed on Ti-Cp foil under potentials of 150 V at a current density of 100 mA/cm2 for 10 min. Multiple characterization techniques were used. X-ray diffraction (XRD) is used to obtain mineralogical phase, scanning electron microscope (SEM) is used to obtain surface morphology, water contact angle (WCA) is used to obtain the wettability of the TiO2, and the chemical absorption of the apatite precipitation was tested using Fourier transform infrared spectroscopy (FT-IR). From the testing results, surface morphology obtained an increased porosity with smaller pore size for TiO2, formed in mixed acids with higher molar concentration. Crystalline hydroxyapatite (HA) was obtained on all mixed solution coatings. Higher apatite precipitation and crystalline were obtained on the TiO2 coating with strong Ti-O- and Ti-OH functional groups, porous surface and strong anatase crystalline.